Efficient wireless power transfer and radio frequency identification systems - Boaventura, Alírio de Jesus Soares (2017)
In the IoT context, where billions of connected objects are expected to be ubiquitously deployed worldwide, the frequent battery maintenance of ubiquitous wireless nodes is undesirable or even impossible. In these scenarios, passive-backscatter radios will certainly play a crucial role due to their low cost, low complexity and battery-free operation. However, as passive-backscatter devices are chiefly limited by the WPT link, its efficiency optimization has been a major research concern over the years, gaining even more emphasis in the IoT context. Wireless power transfer has traditionally been carried out using CW signals, and the efficiency improvement has commonly been achieved through circuit design optimization. This thesis explores a fundamentally different approach, in which the optimization is focused on the powering waveforms, rather than the circuits. It is demonstrated through theoretical analysis, simulations and measurements that, given their greater ability to overcome the built-in voltage of rectifying devices, high PAPR multi-sine (MS) signals are capable of more efficiently exciting energy harvesting circuits when compared to CWs. By using optimal MS signals to excite rectifying devices, remarkable RF-DC conversion efficiency gains of up to 15 dB with respect to CW signals were obtained. In order to show the effectiveness of this approach to improve the communication range of passive-backscatter systems, a MS front-end was integrated in a commercial RFID reader and a significant range extension of 25% was observed. Furthermore, a software-defined radio RFID reader, compliant with ISO18000-6C standard and with MS capability, was constructed from scratch. By interrogating passive RFID transponders with MS waveforms, a transponder sensitivity improvement higher than 3 dB was obtained for optimal MS signals. Since the amplification and transmission of high PAPR signals is critical, this work also proposes efficient MS transmitting architectures based on space power combining techniques. This thesis also addresses other not less important issues, namely self-jamming in passive RFID readers, which is the second limiting factor of passive-backscatter systems. A suitable self-jamming suppression scheme was first used for CW signals and then extended to MS signals, yielding a CW isolation up to 50 dB and a MS isolation up 60 dB. Finally, a battery-less remote control system was developed and integrated in a commercial TV device with the purpose of demonstrating a practical application of wireless power transfer and passive-backscatter concepts. This allowed battery-free control of four basic functionalities of the TV (CH+,CH-,VOL+,VOL-).